Skills of Analysis for The Literacy Texts in The 8th Grade Primary Schools Curriculum in The Region - Qarani, Ahmed M. M. (Humanities Journal of University of Zakho, 2014)
This research identifies the skills of analysis for the literacy texts in the 8th grade primary schools curriculum in the Region. It concentrates on the weaknesses in the current curriculum, which is limited to indoctrinating students with information regarding the life of the writer and his work. Furthermore, it looks into the meanings of the text and the vocabulary. This distances the students from literacy analysis in the curriculum, and hence does not meet the goals of the literacy section in the curriculum which aims to building the capacity of students in literacy analyses, understanding the text and enjoying it. The research is divided into a preface and two sections: The preface looks into the definitions of certain concepts used in this research, these include: Curriculum, development, skills, literacy analysis, analysis skills. The first part of the research looks into the various analytical tools of literature in the curriculum. This includes purpose of the text, idea that the literacy text is generated from: values in the text, type of senses and feelings; the rhythm and units of the literacy text, extracting meanings in the text, identifying the figurative meanings, differentiating the different structural styles. The second part of the research looks into the application of analysis skills on literacy texts in a typical lesson. And finally the most important findings of the research is put forward in the end.